Emergent Completion Pneumonectomy for Postoperative Hemorrhage from Rupture of the Infected Pulmonary Artery in Lung Cancer Surgery. (31st July 2011) - Ayabe, Takanori; Shimizu, Tetsuya; Tomita, Masaki; Yano, Mitsuhiro; Nakamura, Kunihide; Onitsuka, Toshio
Abstract : Completion pneumonectomy (CP) is one of the most difficult procedures and known to be associated with a high morbidity and mortality. A 74-year-old male underwent a left upper lobectomy for pulmonary adenocarcinoma (T3N0M0); six days later after the surgery, he had a sudden postoperative intrathoracic excessive hemorrhage with shock. Emergent redo thoracotomy was performed to treat the bleeding from the ablated interlobar pulmonary artery by suturing with prolene. However, 3 days later after the second operation, he had the second intrathoracic bleeding. Emergent CP was performed with cardiopulmonary bypass by anterior transpericarsial approach via a median sternotomy. The hemorrhage was caused by a rupture of the proximal fragile and infected pulmonary artery. We performed omentopexy for the infected intrathoracic cavity and for covering of the divided main bronchial stump. We had a rare experience of two times of postoperative life-threatening hemorrhage from rupture of the infected pulmonary artery after left upper lobectomy. Emergent CP as salvage surgery should have an advantage in control of infected proximal pulmonary arterial hemorrhage. We should take care of tearing off of adventitia of pulmonary artery in lobectomy because of a possibility of postoperative hemorrhage under a fragility of the injured pulmonary artery with infection.